The Wills Eye Hospital atlas of clinical ophthalmology CD-ROM - Montzka, Daniel P. (Philadelphia : Lippincott Williams & Wilkins, 2001)
Contains the full text and all of the more than 1,400 images from the print atlas. Additionally contains a multitude of reference materials including more than 280 pathology images, over 20 clinical video segments, and 17 video lectures. Covers the principle subjects in ophthalmology including uveitis, strabismus, the retina, and the interior segments. Supplies guidance on interpreting, comparing, and correlating a wide range of diagnostic studies.
Title from disc label
Daniel P. Montzka
System requirements: 200 MHz processor or higher; 32MB of RAM; Windows 95, 98, 2000, or NT; 30MB of hard disk space; Netscape 4.7 or higher with Java settings enabled or Internet Explorer 5.0 or higher higher with Java settings enabled; for QuickTime, Sound Blaster or compatible card and speakers, DirectX version 3.0 or later is recommended.
Keywords: Eye Diseases -- atlases